ANALISIS IMPLEMENTASI STRATEGI PEMASARAN DIGITAL MENGGUNAKAN MODEL SOSTAC PADA PT. ERHA KLINIK INDONESIA - Sulistyowati, Tussi; Ansori, Ansori; Husda, Nur Elfi (Universitas Putera Batam, 2024)
This research employs a qualitative, descriptive methodology to delve into PT. Erha Clinic Indonesia's digital marketing strategies. Through interviews, observations, and documentation, the study utilizes the SOSTAC model, analyzing Situation Analysis, Objectives, Strategy, Tactics, Actions, and Control to comprehensively assess the clinic's digital marketing strategy. The research begins by examining the current state of PT. Erha Clinic Indonesia's digital marketing efforts, aligning them with their objectives. The strategic plan outlines how the clinic targets middle to upper-class individuals throughout Indonesia, aiming to become a recognized leader in the beauty and skin health industry. Leveraging the 4Ps model, PT. Erha Clinic Indonesia offers dermatological services and beauty products with standardized pricing. Additionally, the clinic maintains a strong online presence, with multiple strategically located branches and promotional activities. The content creation process and advertising tools are integral to content dissemination. The clinic continuously monitors performance, ensuring alignment with objectives. In the suggestion section, recommendations are offered to enhance the clinic's digital marketing strategy, including responsive website development, localized social media profiles, content marketing, customer engagement, data analytics utilization, personalized services, and strategic online advertising. Recommendations for clinic customers emphasize staying connected through official platforms, sharing feedback, exploring informative content, and benefiting from seasonal offers. Future research suggestions encompass in-depth channel analysis, customer preference evaluation, competitive landscape exploration, offline marketing assessment, and a comprehensive study of digital marketing implications in the healthcare and skincare sector, including regulatory and ethical aspects.